Lexical-Semantic Grouping Of Embroidery Terms (Eurasian Journal of Humanities and Social Sciences, 2025)
This article analyzes the lexical-semantic system of Uzbek embroidery terms. Lexical units related to embroidery are divided into groups based on meaning, scope, dialectal changes, ethnolinguistic factors, sewing techniques, and elements of material culture. The study shows that embroidery is an important linguistic resource that reflects the historical and aesthetic experience of the people and their place in applied art.